29Si NMR of aqueous silicate complexes at gigapascal pressures. Issue 1 (December 2018) - Pilgrim, Corey; Colla, Christopher; Ochoa, Gerardo; Walton, Jeffrey; Casey, William
Abstract Geochemists have models to predict solute speciation and mineral equilibria in aqueous solutions up to 1200 °C and 6 GPa. These models are useful to uncover reaction pathways deep in the Earth, though experimental confirmation is extremely difficult. Here we show speciation changes among aqueous silicate complexes to pressures of 1.8 GPa through use of a high-pressure solution-state NMR probe. The radiofrequency circuit uses a microcoil geometry that is coupled with a piston-cylinder pressure cell to generate and maintain these high pressures. The 1.8 GPa pressure corresponds to pressures reached at the lower crust or upper mantle. Although these experiments are limited to ambient temperature, we show that the increased pressure affects complexation and oligomerization reactions by eliminating bulk waters and that the pressure effects are completely reversible. Silicates are abundant in the Earth's crust but their high-pressure solution chemistry has not been studied by NMR. Here the complexation chemistry of aqueous silicates is studied at pressures of up to 1.8 GPa by29 Si NMR spectroscopy.